Sexual abuse and physical neglect in childhood are associated with affective theory of mind in adults with schizophrenia - Vaskinn, Anja (Schizophr Res Cogn, 2020)
Whereas childhood trauma is associated with reduced nonsocial cognition in schizophrenia, research on the relationship between childhood trauma and social cognition is limited and mixed. The aim of this study was to examine the association between childhood trauma and theory of mind (ToM) in persons with schizophrenia (n = 68) compared to healthy control participants (n = 70). Childhood trauma was assessed with the Childhood Trauma Questionnaire (CTQ), providing information on physical abuse, emotional abuse, sexual abuse, physical neglect and emotional neglect. ToM was indexed by the Movie for the Assessment of Social Cognition (MASC), which yields scores for total, cognitive and affective ToM, and for three error types (overmentalizing, undermentalizing, no mentalizing). Persons with schizophrenia had elevated rates of childhood trauma and lower ToM scores than healthy controls. In the schizophrenia group, associations between sexual abuse and affective ToM was statistically significant. In regression analyses, physical neglect was found to be the strongest predictor of affective ToM. In healthy controls, childhood trauma was not associated with ToM. Follow-up analyses comparing individuals with/without clinically significant childhood trauma, confirmed the findings for the schizophrenia group. No causal inferences can be made in this cross-sectional study, but the results suggest an illness-specific association between both sexual abuse and physical neglect in childhood, and adult affective ToM in individuals with schizophrenia.